Back to Basics: Developmental Catalysts of Quality Improvement in Early Education and Care. (October 2021) - Hanno, Emily C.; Jones, Stephanie M.; Lesaux, Nonie K.
Children's experiences in early education programs can have a profound influence on their cognitive, social, and emotional development. In these settings, interactions with educators serve as catalysts for children's healthy development. Yet too few children today are in the types of high-quality early learning environments marked by warm, cognitively stimulating exchanges. This review summarizes research on the features of settings that promote growth in children's skills across a range of developmental domains, then describes research documenting these features across today's early education and care landscape. Turning to strategies for cultivating these features across the diverse early education and care system, the discussion focuses on the central role of the educator. The conclusion draws implications for ongoing public preK expansion and quality improvement efforts, as well as highlights opportunities for future research to further these efforts.